Diversity of Snow Bacteria from the Zangser Kangri Glacier in the Tibetan Plateau Environment. Issue 1 (2nd January 2017) - Yan, Peiying; Hou, Shugui; Qu, Jianjun; Chen, Tuo; Wang, Yetang; Zhang, Shuhong
ABSTRACT: Bacterial abundance and community diversity were investigated in a snow pit on the Zangser Kangri (ZSGR) glacier on the Tibetan Plateau by epifluorescence microscopy and small subunit 16 S rRNA gene sequence analyses. Cell abundance and bacterial colony-forming units (CFUs) ranged from 3 × 10 3 to 1.5 × 10 4 cells/ml and 0 to 2.2 CFU/ml, respectively. All isolates were classified into four major groups: Actinobacteria (68%), Alphaproteobacteria (18%), Gammaproteobacteria (9%) and Firmicutes (5%). Principal component analysis of the biochemical data combined with linear correlation analysis revealed two main sources of bacteria on the ZSGR glacier. Considerable amounts of bacteria were probably emitted by vegetation of Qangtang Grassland and transported by the Indian monsoon, some of which might have originated from the Taklimakan Desert and undergone long-range transportation by westerly winds. Bacterial abundance was positively correlated with both Ca 2+ and HCOO − concentrations, suggesting two microbial transport carriers, including mineral and organic particles. Members of Caulobacter and Roseomonas that participate in nitrogen transformations were observed in the uppermost snow pit layer, suggesting that they are involved in nitrogen cycling on this glacial surface.